MEMBANGUN RENCANA STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI PADA UNIVERSITAS TEKNOLOGI SUMBAWA - Esebella, Shinta (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
The purpose of this research is to develop a beneficial Information Technology Strategy Plan and Information System (IS/IT) as a part of evaluation in elaborating IS/IT within Sumbawa University of Technology in the future. In which, this research applies Ward and Peppard Models as a method of analysis and strategy in developing the plan of IS / IT that is in line with the strategy plan of Sumbawa University of Technology 2016-2019. The framework used in the analysis process in the internal environment is the Critical Success Factor (CSF) framework and the PEST framework (Political, Economic, Social, and Technological) to analyze the external environment. Moreover, the result of this research is expected to be portfolio guidance in advancing SI / IT that is able to be used to determine the leadership policy at Sumbawa University of Technology in ascertaining the maintenance process and the development of SI / IT to support the plan in harmony with the university mission.